Integrative taxonomy elucidates the species of Proloricaria (Siluriformes: Loricariidae) - Vitor H. P. Pinheiro; Carolina B. Machado; Júlio C. Garavello; Pedro M. Galetti Jr.; Alexandre K. de Oliveira (Neotropical Ichthyology)
Abstract The genus Proloricaria is widely distributed throughout the upper Paraná River drainage. Its type-species, Loricaria prolixa, was described from specimens of the Tietê River basin, and the other species, P. lentiginosa, was originally described as L. prolixa lentiginosa, from specimens of the Grande River basin. The two species exhibit considerable morphological similarity and, since their description, there are doubts regarding their recognition and taxonomic validity. In this study, an integrative taxonomy approach was employed to distinguish and delimit the species through both morphological analyses of specimens from collections and molecular analyses of recently collected specimens, as well as published genetic data. Morphologically, the two species are primarily differentiated by color pattern and the presence of a pair of anterior pre-dorsal plates in P. lentiginosa, which are absent in P. prolixa. Molecular analyses further support the taxonomic validity of the two species, revealing an interspecific genetic distance of 3.1%. The species are redescribed, and references to both in the literature, and their distribution in the upper Paraná River basin, are reviewed. Proloricaria prolixa is distributed across the Tietê, Paranapanema, Paraná and Paranaíba river basins, whereas P. lentiginosa is found in the Grande and Paranaíba river basins.